2010
DOI: 10.3233/jad-2010-1304
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Increased Iron Intake During the Neonatal Period on the Brain of Adult AβPP/PS1 Transgenic Mice

Abstract: The present study was aimed to investigate neuropathological changes in AbetaPP/PS1 transgenic mice (Tg), as a model of Alzheimer's disease, subjected to supplementary iron administration in a critical postnatal period, in order to reveal the interaction of genetic and environmental risk factors in the pathogenesis of the disease. Twelve Tg and 10 wild-type (Wt) littermates were administered iron between the 12th and 14th post-natal days (TgFe, WtFe); 11 Tg and 15 Wt received vehicle (sorbitol 5%) alone in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…Accordingly, we have previously shown that adult iron-treated rats show increased oxidative damage in the hippocampus and cortex (de Lima et al 2005a;Dal-Pizzol et al 2001), areas in which we now observe increased apoptosis at the same life period. We have also shown in prior studies that at this period iron-treated animals have increased GFAP-immunoreactivity in equivalent brain areas (Fernandez et al 2009), suggesting an active glyosis that we may speculate are taking over spaces left by neuronal death.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Accordingly, we have previously shown that adult iron-treated rats show increased oxidative damage in the hippocampus and cortex (de Lima et al 2005a;Dal-Pizzol et al 2001), areas in which we now observe increased apoptosis at the same life period. We have also shown in prior studies that at this period iron-treated animals have increased GFAP-immunoreactivity in equivalent brain areas (Fernandez et al 2009), suggesting an active glyosis that we may speculate are taking over spaces left by neuronal death.…”
Section: Discussionmentioning
confidence: 71%
“…The cognitive deficits resulting from iron supplementation were accompanied by an increased oxidative damage in brain regions (de Lima et al 2005a). We have also demonstrated that neonatal iron supplementation in mice can lead to increased GFAP immunoreactivity in adulthood, suggesting a reactive gliosis response that could be following oxidative damage-induced neuronal loss (Fernandez et al 2009). …”
Section: Introductionmentioning
confidence: 93%
“…At 6 months of age, these iron-exposed mice exhibited greater astrogliosis than did animals not exposed to iron, but showed no increase in plaque density. 92 However, this study did not assess cognitive outcomes or levels of oligomerized Aβ.…”
Section: Contribution Of Early-life Exposurementioning
confidence: 99%
“…Although these results suggest a permanent cellular defense to transient iron overload during development, it may be questioned whether these changes are protective or facilitators of later brain damage. Absence of increased b-amyloid, phosphorylated tau and a-synuclein in iron-treated rats (data not shown) and also in wild type iron-treated mice (Fernandez et al 2010) are indicators of a scenario consistent with a successful adaptative response. Recent research demonstrated that amyloid plaques in APP/PS1 mice bind less metal than plaques in human AD and this probably represents a difference in the process of neurodegeneration (Leskovjan et al 2009).…”
Section: Discussionmentioning
confidence: 86%
“…Comparisons between groups were performed using the independent samples t test. **P \ 0.01 in APP/PS1 and wild-type littermates as well (Fernandez et al 2010). In humans, Smith et al (2010) found altered redox iron in mild cognitive impairment (MCI) and preclinical cases of AD suggesting an important and early contribution to the disease process before significant cognitive decline and the amount of redox metal accumulation was associated with glial cells detected by GFAP immunofluorescence.…”
Section: Discussionmentioning
confidence: 98%